Impact of Ambient and Elevated [CO(2)] in Low Light Levels on Growth, Physiology and Nutrient Uptake of Tropical Perennial Legume Cover Crops - Baligar, Virupax C. (Plants (Basel), 2021)
At early stages of establishment of tropical plantation crops, inclusion of legume cover crops could reduce soil degradation due to erosion and nutrient leaching. As understory plants these cover crops receive limited irradiance and can be subjected to elevated CO(2) at ground level. A glasshouse experiment was undertaken to assess the effects of ambient (450 µmol mol(−1)) and elevated (700 µmol mol(−1)) levels of [CO(2)] on growth, physiological changes and nutrient uptake of six perennial legume cover crops (Perennial Peanut, Ea-Ea, Mucuna, Pigeon pea, Lab lab, Cowpea) under low levels of photosynthetic photon flux density (PPFD; 100, 200, and 400 µmol m(−2) s(−1)). Overall, total and root dry biomass, total root length, specific leaf area, and relative growth rates were significantly influenced by levels of [CO(2)] and PPFD and cover crop species. With few exceptions, all the cover crops showed significant effects of [CO(2)], PPFD, and species on net photosynthesis (P(N)) and its components, such as stomatal conductance (gs) internal CO(2) conc. (Ci), and transpiration (E). Increasing [CO(2)], from 450 to 700 μmol mol(−1) and increasing PPFD from 100 to 400 μmol ּm(−2) ּs(−1) increased P(N). Overall, the levels of [CO(2)], PPFD and species significantly affected total water use efficiency (WUE(TOTAL)), instantaneous water use efficiency (WUE(INST)) and intrinsic water use efficiency (WUE(INTR)). With some exceptions, increasing levels of [CO(2)] and PPFD increased all the WUE parameters. Interspecific differences were observed with respect to macro-micro nutrient uptake and use efficiency. With a few exceptions, increasing levels of [CO(2)] from 450 to 700 μmol mol(−1) and PPFD from 100 to 400 μmol m(−2) s(−1) increased nutrient use efficiency (NUE) of all nutrients by cover crop species.